Uncertainty in economic theory essays in honor of David Schmeidler's 65th birthday - Gilboa Itzhar (London Routledge, 2004)
This volume brings together important papers, coupled with new introductions, in the massively influential area of uncertainty in economic theory. Seminal papers are available together for the first time in book format, with new introductions and under t
Keywords: Choice (Psychology); Decision making; Mathematical models; Risk management; Uncertainty